OBJECTIVES, TASKS AND PRINCIPLES OF EFFICIENT MANAGEMENT OF ENTERPRISES - Ikromovich , Irgashev Dilmurod (International Journal of Psychosocial Rehabilitation, 2020)
The article examines in detail the existing approaches to understanding the specifics of corporate profit management, the structure of profit management, the views of economists on profit management, the process of the principles of profit management in enterprises.